Practical applied mathematics : modelling, analysis, approximation - Howison, Sam (Cambridge texts in applied mathematics., 2005)
Used either by upper-undergraduate students, or as extra reading for any applied mathematician, this book illustrates how the reader's knowledge can be used to describe the world around them. Topics include distributions, asymptotic methods and the basics of modelling. Applications range from piano tuning to egg incubation and traffic flow.